The power of hormones : the new science of how hormones impact every aspect of our health - Nieuwdorp, Max, 1977- (Simon Element, 2024)
"Hormones rule our lives. From conception, to birth, to our last breath, hormones control the delicate processes that keep our bodies in balance. However, when this careful stasis is disturbed, our hormones can wreak havoc on our health. Max Nieuwdorp, MD, PhD, knows exactly what signals your hormones are sending you and how they impact how you look, feel, and behave. In this foundational guide to hormonal health, he breaks down how hormones impact every system in the body, empowering you with the knowledge you need to get to the root of chronic health problems and set yourself up long lasting, sustainable wellness. Inspired by Dr. Nieuwdorp's day-to-day interaction with his patients, The Power of Hormones describes hormonal health in a detailed and accessible style, helping you clue in to symptoms of hormonal imbalance such as persistent fatigue and weight gain. His unique approach advocates for considering the far-reaching roles played by hormones throughout the body and is a go-to guide for understanding how they influence our health, our lives, and who we are."--